Hsa_circ_0060927 Is a Novel Tumor Biomarker by Sponging miR-195-5p in the Malignant Transformation of OLK to OSCC - Xu, Siming; Song, Yuhan; Shao, Yanxiong; Zhou, Haiwen (Frontiers in Oncology, 2022)
Objective To investigate the clinical significance of differentially expressed circRNAs and candidate circRNAs in the transformation of oral leukoplakia (OLK) to oral squamous cell carcinoma (OSCC). Methods We performed high-throughput circRNA sequencing in six cases of normal oral mucosal (NOM) tissues, six cases of OLK tissues, and six cases of OSCC tissues. Ten circRNAs with significant differential expression were verified by qRT-PCR. Enzyme tolerance assay and Sanger sequencing were performed on the screened target circRNA hsa_circ_0060927, and a qRT-PCR assay of hsa_circ_0060927 was performed in three tissues (24 cases in each group); this was followed by an ROC analysis. The ceRNA network was predicted using TargetScan and miRanda. MiR-195-5p and TRIM14 were selected as the downstream research objects of hsa_circ_0060927. The sponge mechanism of hsa_circ_0060927 was detected by AGO2 RIP. The interaction between hsa_circ_0060927 and miR-195-5p was verified by RNA pull-down assay and dual luciferase reporter gene assay. The expressions of hsa_circ_0060927, miR-195-5p, and TRIM14 were verified by normal oral epithelial primary cells and cell lines of LEUK1, SCC9, and SCC25. The hsa_circ_0060927 overexpressed plasmid and miR-195-5p mimics were constructed to transfection LEUK1 to detect the changes in cell proliferation, apoptosis, and migration. Results The results of qRT-PCR validation were consistent with the sequencing results. Hsa_circ_0060927 is a true circRNA with trans-splicing sites. The expression of hsa_circ_0060927 increased in NOM, OLK, and OSCC. Overexpression of hsa_circ_0060927 enhanced the ability of cell proliferation and migration, and decreased cell apoptosis capacity. The prediction of ceRNA network suggested that hsa_circ_0060927 could regulate the target gene TRIM14 through sponging miR-195-5p. AGO2 RIP indicated that hsa_circ_0060927 had a sponge mechanism. RNA pull-down and dual luciferase reporter gene assay suggested that hsa_circ_0060927 interacted with miR-195-5p. Hsa_circ_0060927 was positively correlated with the expression of TRIM14, and could relieve the inhibition of miR-195-5p on TRIM14 to regulate cell proliferation, apoptosis, and migration of LEUK1 cells. Conclusion Hsa_circ_0060927 acted as a potential key ceRNA to sponge downstream miR-195-5p and promote OLK carcinogenesis by upregulating TRIM14. Hsa_circ_0060927 was expected to be a molecular marker for the prevention and treatment of OLK carcinogenesis through the hsa_circ_0060927/miR-195-5p/TRIM14 axis.